Threeing: Incorporating "Relational Circuits" into the Research Encounter. (28th July 2017) - Mendonca, Karl Julius; Russell, Morgan
Abstract: In the field of design research, the ethnographic field visit is no longer a solo, intimate encounter between the researcher and her subject(s). More often than not, it is a choreographed event that involves the participation of a broader milieu of stakeholders and team members that span a gamut of roles and hierarchies. The active participation of "non-ethnographers" in the research process has been both championed and an area of scrutiny and reservation. In the pro-participation camp, we have arguments that emphasize the value of embodied knowledge over synthesized reports. Conversely, we hear about a fair number of risks that need to be mitigated in the form of cautionary tales, where "non-ethnographers" have unwittingly broken basic protocols by speaking over research subjects or hi-jacked an interview. While adequate preparation with stakeholders is key for both camps, a deeper analysis of the configuration between the "ethnographer, " "research participant" and "non-researcher" is typically of secondary importance to the methodological imperative. In short, there is surprisingly little attention paid to the question of group dynamics, so to speak. Designed for artists, ethnographers, educators and designers, this lecture demonstration will introduce the idea of a "relational circuit" elaborated by video artist and cybernetician Paul Ryan based on semiotician Charles Pierce's three modes of being (firstness, secondness and thirdness), as one possible theoretical model to address this lacuna. Ryan's "three person solution" is unique in that it seeks to provide a "non-competitive and asymmetric" approach to collaboration that is fluid, where participants are able to navigate between roles using props and rules. The practice of "threeing" is both engaging and fun, in that the flow of conversation and activity builds towards collectively generated insights that allow for collaboration without conflict..